KEANEKARAGAMAN SPESIES HERPETOFAUNA PADA BERBAGAI TIPE TUTUPAN LAHAN DI LANSEKAP PERKEBUNAN SAWIT: Studi Kasus di PT. BLP Central Borneo - Rozza Tri Kwatrina (Graduate School Bogor Agricultural University (SPs IPB), 2019)
The expansion of oil palm plantations in Indonesia is often blamed as the drivers of natural resource destruction and decrease the tropical biodiversity. Herpetofauna is one of biodiversity on oil palm plantation, but information about its species diversity is still limited. This research was aims to reveal the variation of diversity of Herpetofauna on oil palm landscape in central Borneo. Field inventory was conducted on seven types of land cover i.e. young oil palm, mature oil palm, old oil palm, High Conservation Value area, secondary forest, shrubs, and smallholder plantation. We used Visual Encounter Method to invent Herpetofauna spesies on all land cover type. This study reveal that the diversity of Herpetofauna species in PT BLP varies by land cover type. The land cover types of HCV and Secondary Forest have the largest number of species (12 species). Secondary Forest is the type of land cover with the highest abundance among other types of land cover, followed by old oil palm plantations. The oil palm plantations lanscape with different type of land cover can be part of the habitat for several Herpetofauna species and managed for sustainable oilpalm scheme.